Relationships of wood anatomy with growth and wood density in three Norway spruce clones of Finnish origin - Luostarinen, Katri; Pikkarainen, Laura; Ikonen, Veli-Pekka; Zubizarreta Gerendiain, Ane; Pulkkinen, Pertti; Peltola, Heli (NRC Research Press, 2017)
The relationships between anatomical characteristics of wood, growth, and wood density were studied in three Finnish Norway spruce (Picea abies (L.) Karst.) clones, which had differences in average stem volume and wood density. This was done to determine which anatomical characteristics are affected by growth and which affect wood density and to determine if clones of different geographical origins (Southeastern, C43; Southern, C308; Southwestern, C332) differ from each other in these respects. In this study, tracheid double wall thickness, lumen diameter, and wall to lumen ratio, numbers, sizes, and percentages of resin canals, and numbers of rays were correlated with ring, earlywood, and latewood widths and densities. The wood density correlated positively with the wall to lumen diameter ratio. Rapid growth decreased the number of rays independently of the clone. Furthermore, the effects of growth on the number and size of resin canals depended strongly on the clone. C332 had very thin tracheid walls in latewood, which decreased wood density. However, the high number of rays and resin canals increased it. Growth significantly influences wood anatomy and, consequently, wood density. Hence, wood anatomy should be considered in the selection of proper genotypes for forest cultivation in a changing growing environment.
Keywords: ray; Picea abies; xylem; tracheids; resin canals